The Effect of Intellectual Capital and Literacy of Sharia Bank on the Decision to Be a Customer of BSI KCP Aek Kanopan - Sari, Mutiara; M. Nawawi, Zuhrinal; Inayah, Nurul (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this study is to determine the effect of Islamic competence and intellectual capital on customer decisions. This study uses quantitative methods to determine the relationship and influence between variables. The population used in this study were 223 customers of Bank BSI KCP Aek Kanopani and the number of samples was selected from the Slovin formula. The data collection technique for this study used a questionnaire or distributed questionnaires to determine the effect of intellectual capital and Islamic banking knowledge on the decision to become a customer of BSI KCP Aek Kanopan. During data analysis, variable calculations were performed using SPSS version 23.0. The results of this study indicate that the intellectual capital variable has no effect on customer decisions, the literacy variable has a significant effect on customer decisions.